The legal value of the administrative judge's role in establishing legal rules - Amin, Asst.L.Chenar Jabbar Mohammed Amin (Sulaimani Journal for Humanities, 2025)
Perhaps the first task of the judge is to strive to achieve justice and apply the law in administrative cases. He bases this on the data of the cases presented, the jurisprudential works that the judge can use to apply the judicial rule, as well as the objective sources that the judge can rely on to deduce the judicial ruling. He seeks, through his striving, to resolve administrative disputes and at the same time adds other solutions to the administrative judicial record. Therefore, the administrative judge's striving is a major source of the legal rule in administrative cases. However, this striving has no meaning without examining its legal value so that the judge can issue the rulings and decisions that establish legal rules. Studying the legal value of the judge's role in this field requires a precise analysis of the presented fact and consideration of the public interest, rights, and freedoms. Therefore, we find that the administrative judge is unique in his work towards judicial striving, and perhaps the source of this is the nature of administrative law, as it is flexible and constantly changing based on the development of the public needs of society.
Keywords: Administrative judge; judicial precedent; legal rule; legal value of judicial precedent